P-399 Effect of male body mass index on miscarriage rate following fertility treatment, a systematic review and meta-analysis. (30th June 2022) - Halimeh, R; Chronopoulou, E; Duran, M; Saab, W; Serhal, P; Seshadri, S
Abstract: Study question: Is raised paternal body mass index (BMI) important for the miscarriage rate following assisted reproductive technology (ART)? Summary answer: Based on the available evidence, raised male BMI is not associated with higher risk of miscarriage following ART. What is known already: More than half women and men of reproductive age worldwide are overweight or obese.There is extensive literature exploring the importance of normal female BMI for reproductive outcomes. However, little attention has been given to male BMI for couples seeking fertility treatment [1] .The adverse effect of male obesity on sperm parameters including DNA damage is well documented and there is evidence suggesting that raised male BMI results in significant decrease in live birth rate following ART [2] .Furthermore, emerging evidence from human and animal studies demonstrates that paternal obesity can affect the future health of the offspring through epigenetic pathways[3]. Study design, size, duration: A computerized literature search was performed using EMBASE, MEDLINE, CINAHL and the Cochrane Central register of trials from database inception to November 2021. The aim was to explore the association between male BMI on miscarriage rate following ART. Reference lists of relevant studies were cross-checked. Only articles with full manuscripts available and published in English were included. Papers not relating to human subjects were excluded. All eligible studies were included (observational, prospective and retrospective studies). Participants/materials, setting, methods: Included studies reported on couples undergoing ART for any indication using partner's fresh sperm. Outcomes of interest were miscarriage rate and clinical pregnancy rate. Outcome data from each study were pooled and expressed as odds ratio (OR) with 95% confidence interval (CI) by using a random-effect model due to statistical heterogeneity in the outcome data[4]. Heterogeneity of treatment effects was evaluated using the I2 statistic to quantify the variation across studies caused by heterogeneity. Main results and the role of chance: Abstract screening identified 197 relevant studies. After excluding duplicates, reviews and studies which did not fulfill the inclusion criteria, full manuscripts were accessed for 13 studies. Six studies were identified exploring the effect of male BMI on miscarriage following ART, two prospective and four retrospective. The quality of evidence was low using the GRADE framework. Meta-analysis was possible for three studies including 6793 couples undergoing ART. Outcomes were compared for male BMI < 25 kg/m2 versus BMI >/=25 kg/m2 . The pooled results did not show a statistically significant increase in miscarriage rate when the male partner was overweight or obese compare to normoweight (OR 1.32, 95% CI 0.82–2.1, P = 0.249). There was significant heterogeneity between the included studies (I 2 = 48.7%). There was no significant effect of male BMI on clinical pregnancy rate (OR 0.90, 95% CI 0.59–1.38, P = 0.637). For two of the remaining studies which could not be included in the meta-analysis due to missing data, the authors concluded that male BMI >25 was not associated with increased miscarriage risk whilst the most recent prospective study showed that high male BMI was associated with increased risk of chromosomal aberration-related miscarriages. Limitations, reasons for caution: The number of the included studies and significant heterogeneity are the main limitations. It was not possible to account for important confounders such as age, subfertility diagnosis, type of stimulation and laboratory parameters including embryo grade. We grouped participants in two BMI categories therefore did not distinguish between overweight/obesity/morbid obesity. Wider implications of the findings: Despite increasing evidence suggestive of adverse effect of raised male BMI on reproductive outcomes, there is limited literature exploring the impact on miscarriage rate following ART. More well-designed studies are needed for sound conclusions. Paternal characteristics, general health and preconception lifestyle should not be overlooked in the fertility consultation. Trial registration number: not applicable